2021
DOI: 10.1186/s13287-021-02505-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β primed mesenchymal stromal cells moderate hemorrhagic shock-induced organ injuries

Abstract: Background Organ damages following hemorrhagic shock (HS) have been partly attributed to an immunological dysfunction. The current challenge in the management of HS patients is to prevent organ injury-induced morbidity and mortality which currently has not etiological treatment available. Mesenchymal stromal cells (MSC) are used in clinical cell therapy for immunomodulation and tissue repair. In vitro priming is often used to improve the immunomodulation efficiency of MSC before administration.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The few studies using MSCs in THS showed that their administration early after hemorrhagic +/− traumatic shock limited vascular permeability by preserving the barrier junction proteins (VE-cadherin, claudin-1, and occludin-1), inhibiting the expressions of leukocyte adhesion molecules (VCAM-1 and ICAM-1) on endothelial cells, and decreasing both serum concentrations of inflammatory molecules and CD68- and MPO-positive cell tissue infiltration ( 17 ). We recently showed that IL-1β-primed MSCs attenuated hemorrhagic shock-induced early hepatic and kidney injury and dysfunction and reduced the SIRS/CARS syndrome, as shown by the decreases in the plasma cytokine concentrations and the phenotypic activation of circulating CD11bc + cells ( 242 ). MSCs would also prevent the decrease in hematopoietic progenitors induced by THS in the bone marrow ( 15 , 17 , 243 ).…”
Section: Msc-derived Extracellular Vesicles: Toward Cell-free Therapeutic Applicationsmentioning
confidence: 99%
“…The few studies using MSCs in THS showed that their administration early after hemorrhagic +/− traumatic shock limited vascular permeability by preserving the barrier junction proteins (VE-cadherin, claudin-1, and occludin-1), inhibiting the expressions of leukocyte adhesion molecules (VCAM-1 and ICAM-1) on endothelial cells, and decreasing both serum concentrations of inflammatory molecules and CD68- and MPO-positive cell tissue infiltration ( 17 ). We recently showed that IL-1β-primed MSCs attenuated hemorrhagic shock-induced early hepatic and kidney injury and dysfunction and reduced the SIRS/CARS syndrome, as shown by the decreases in the plasma cytokine concentrations and the phenotypic activation of circulating CD11bc + cells ( 242 ). MSCs would also prevent the decrease in hematopoietic progenitors induced by THS in the bone marrow ( 15 , 17 , 243 ).…”
Section: Msc-derived Extracellular Vesicles: Toward Cell-free Therapeutic Applicationsmentioning
confidence: 99%
“…On one hand, MSCs can improve the microenvironment via the direct effect of cytokines, chemokines, extracellular vesicles, and exosomes [ 37 ]. Our previous study has shown that proper pretreatment enhanced the therapeutic effect of MSCs by regulating anti-inflammatory agents in the exosome [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several in vitro and in vivo studies, IL-1β priming maximized the immunomodulation effect of MSCs by regulating IL-6 and IL-8 expression and influencing the polarization of peritoneal macrophages ( 65 , 66 ). Moreover, systemic cytokines (IL-1α, IL-6, and IL-10) and the programmed cell death receptor (PD)-1/PD-L1 axis were decreased by IL-1β-primed MSCs on monocytes and granulocytes in HS-induced kidney and liver injury model ( 53 ). Similarly, the IL-6 concentration also decreased with adipose-derived stem cell treatment in HS-induced liver injury ( 54 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%